Classical Tradition in the Neo-Latin Epithalamium of the Grand Duchy of Lithuania - Šarkauskienė, Skirmantė (Respectus Philologicus, 2003)
This article deals with the characterization of the development of the epithalamium genre in the Classical literature, its imitation and the modification of the contents and the form in the Renaissance and Baroque occasional neo-Latin literature of the Grand Duchy of Lithuania (GDL). There were lyrical and epical (mythological-narrative and rhetorical-panegyric) models of epithalamium genre in the Classical literature. In the 16th century the tradition of the classical epic epithalamium was modified in the Joannes Vislicencis, Petrus Royzius and Joannes Radvanus's wedding poems. Adam Schroter, Stanislaus Cossutius and the Vilnius Academy students synthesized the poetics and stylistics of other genres, such as the elegy, the epigram and the publicist writing in their epithalamia. In the 17th century the traditional conception of the genre, i.e. epithalamium, composed as a verse or a little poem, remained in Mathias Casimirus Sarbievius's nuptial panegyrics. Various kinds of the wedding publications appeared in the surroundings of the Vilnius Academy, where the prose and the poetry were combined. The poetical insertion could be any classical genre such as a dithyramb, the forms of poesis artificiosa, and the epic poems. The Baroque epithalamium quite often took form of the drama or the theatrical staging. The poetics and stylistics of other popular genres such as the emblem, the armorial poetry were frequently used in epithalamia. The evolution of the content of the genre, i.e. the modification of certain topics of the classical epithalamium was influenced by the historical circumstances and political problems of the epoch. The laudation of the wedlock, the encomia for the newly-weds and the prayers became of great actuality. The sovereigns' and noblemen's marriage in the laudation of the wedlock was considered to be not as a personal one but as an important public event, often even identified with the peace between the two states. The newly-weds' encomia reflect the scale of values of the time. The descriptions like the groom's status, the origin, the family's glory, the merits and inner features such as generosity, wisdom, brevity, and piety were accentuated. The bride's spiritual beauty, her chastity, modesty, morality, piety was praised while representing her but not her physical appearance. The prayers, wishing goodness for the married couple, were associated with aspirations of the entire country.
Keywords: an epithalamium; the epical and the lyrical models of the classical epithalamium; the topics; Renaissance; Baroque; he neo-Latin epithalamium of the GDL; classical tradition, its imitation, modification